Uganda Economic Update, July 2017 : Infrastructure Finance Deficit - World Bank (World Bank, Washington, DC, 2017)
As a result of a number of internal and external shocks, Uganda's economy is currently growing at the lowest rate recorded over the past two decades. Therefore, current policy is focused on the management of these impacts so that they do not exacerbate macroeconomic instability and on measures to stimulate the economy to increase growth. The Government's investment push is intended to address binding constraints on growth, with the most significant of these constraints being Uganda's huge infrastructure deficit. The first part of this Ninth Uganda Economic Update presents an assessment of the current state of the economy, while the second part addresses a specific theme related to Uganda's development challenges and the manner in which these may be addressed. This focusses on how the management of Public-Private Partnerships (PPPs) can support Uganda's investment push by facilitating access to private sector financing, by managing the risks intrinsic in these arrangements, and by maximizing the economic and social value of these partnerships. This can only be achieved if the government is committed to building the appropriate set of frameworks to create a conducive environment for private investments and to adopting robust project identification, screening, procurement and contract management processes.